Teratogenic Effect of Smokeless Tobacco on the Gonads of Albino Rats - Sah, Surendra Kumar; Haider, Sayed Javed; Chaudhary, Deepak (Journal of Nobel Medical College, 2024)
Background: Teratogens are substances that, when exposed to a pregnant woman, may result in a physical or functional abnormality in the human embryo or fetus. Caffeine, cocaine, tobacco and alcohol are common teratogens. Teratogenecity depends upon the duration of exposure and amount of teratogens. Smokeless tobacco is a tobacco product used other than smoking such as chewing, sniffing or placing the product between the gum and the cheek or lips.Materials and Methods: This is a experimental study conducted from September 2023 to August 2024 where sixty healthy adult albino rats (11 - 13 weeks old) weighing between 150 -200 gm were bought and reared in the animal house of Anatomy department of Nobel Medical College and all the rats were randomly divided into three equal groups; a control group and two experimental groups (E1 & E2) where E1 were fed with Rajnigandha and E2 were fed with Bhola gutkha as the test materials. Statistical analysis was done in SPSS version 19. All the data were expressed as mean±SD.Results: Reduction in gross body weight from initial (163±10.59gm) to (149.50±13.83gm), volume from (3.50±0.52cc) to (2.50±0.52cc) and diameters of seminiferous tubules from (348.05±23.33µm) to (208.30±12.30µm) and ovarian follicles from (21.35±3.83µm) to (20.74±2.55µm) and reduction of sex ratio in the experimental groups.Conclusion: The study conclude that the smokeless tobacco have a wide range of effects on the overall reproductive functions of the Albino rats and low birth weight baby along with reduction in sex ratio which implies that it directly have bad effects on the human reproductive health.